A Survey of Medical Students' Use of Nutrition Resources and Perceived Competency in Providing Basic Nutrition Education. (6th August 2015) - Connor, Rebecca; Cialdella-Kam, Lynn; Harris, Stephanie R.
Abstract : Purpose. The aims of this study were to assess where medical students obtain their nutrition information and their self-perceived level of competency in providing basic nutrition education to patients. Methods. A survey was distributed to all first through fourth year medical students at Case Western Reserve University (n = 657 ). For statistical analysis, data was expressed as percentages of total responses and binomial regression was used to answer the study hypotheses. Results. The survey response rate was 47%. Forty-two percent of respondents selected a majority of professional nutrition resources (n = 132 ) as their most commonly used nutrition resources, 38% selected a majority of consumer resources (n = 119 ), and 20% selected "I do not use nutrition resources" (n = 61 ). The most popular nutrition resource selected was consumer websites. Seventy percent of respondents reported feeling competent in their ability to provide basic nutrition education to patients (n = 219 ). Conclusion. Medical students seem to feel competent in their ability to give basic nutrition education to patients, but they may be obtaining nutrition information from unreliable consumer-based resources. To help increase the provision of sound nutritional guidance, medical students should be taught to use reliable nutrition resources, as well as the value of referring patients to registered dietitians.